Consumer-Optimal Information Design - Jonas von Wangenheim (Ludwig-Maximilians-Universität München und Humboldt-Universität zu Berlin, Collaborative Research Center Transregio 190 - Rationality and Competition, 2017)
In many trade environments - such as online markets - buyers fully learn their valuation for goods only after contracting. I characterize the buyer-optimal ex-ante information in such environments. Employing a classical sequential screening framework, I find that buyers prefer to remain partially uninformed, since such an information structure induces the seller to set low prices. For the optimal information signal, trade is efficient, and the seller only extracts the static monopoly profit. Further, I fully characterize all possible surplus divisions that can arise in sequential screening for a given prior.
Keywords: D82; 330; information disclosure; sequential screening; strategic learning; bayesian persuasion; mechanism design